2012
DOI: 10.2147/copd.s29571
|View full text |Cite
|
Sign up to set email alerts
|

Proposing a standardized method for evaluating patient report of the intensity of dyspnea during exercise testing in COPD

Abstract: BackgroundMeasuring dyspnea intensity associated with exercise provides insights into dyspnea-limited exercise capacity, and has been used to evaluate treatment outcomes for chronic obstructive pulmonary disease (COPD). Three patient-reported outcome scales commonly cited for rating dyspnea during exercise are the modified Borg scale (MBS), numerical rating scale for dyspnea (NRS-D), and visual analogue scale for dyspnea (VAS-D). Various versions of each scale were found. Our objective was to evaluate the cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
34
0
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(40 citation statements)
references
References 37 publications
3
34
0
3
Order By: Relevance
“…In contrast, we also found that the reduction in SpO2 was not significantly correlated with the Distance 6MWT, which is consistent with the findings of previous studies of World Medical Association (2013) and Camargo et al 7,12,13 The 6MWT includes two objective parameters: walk distance (6MWD) and oxygen saturation (SpO2). Georgiopoulou et al and Borghi-Silva et al, reported that under the influence of a pulmonary rehabilitation program, improve heart rate in exercise and lower heart rate at rest.…”
Section: Discussionsupporting
confidence: 92%
“…In contrast, we also found that the reduction in SpO2 was not significantly correlated with the Distance 6MWT, which is consistent with the findings of previous studies of World Medical Association (2013) and Camargo et al 7,12,13 The 6MWT includes two objective parameters: walk distance (6MWD) and oxygen saturation (SpO2). Georgiopoulou et al and Borghi-Silva et al, reported that under the influence of a pulmonary rehabilitation program, improve heart rate in exercise and lower heart rate at rest.…”
Section: Discussionsupporting
confidence: 92%
“…Procedure Dyspnoea is measured using either the 10-point Borg scale (CR-10) [153] or a 100-mm visual analogue scale (VAS) [154,155]. The CR-10 scale is derived from the original Borg 6-20-point perceived exertion scale (corresponding to a heart rate range of 60-200 bpm) [155,156], modified to an open-ended 10-point scale including written indicators of severity to anchor specific numbers on the scale [153].…”
Section: Dyspnoeamentioning
confidence: 99%
“…The CR-10 scale is derived from the original Borg 6-20-point perceived exertion scale (corresponding to a heart rate range of 60-200 bpm) [155,156], modified to an open-ended 10-point scale including written indicators of severity to anchor specific numbers on the scale [153]. This was updated in 2010 with categories similar to the original 1982 scale, but having 19 points [155,156]. In addition, a "modified CR-10 Borg scale", which is not open-ended, is frequently used [155,156].…”
Section: Dyspnoeamentioning
confidence: 99%
See 2 more Smart Citations